2010
DOI: 10.1074/jbc.m109.086587
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Mitochondrial Membrane Potential by Mitochondrial Insertion of Granzyme B and Direct Hax-1 Cleavage

Abstract: The cytoplasm and the nucleus have been identified as activity sites for granzyme B (GrB) following its delivery from cytotoxic lymphocyte granules into target cells. Here we report on the ability of exogenous GrB to insert into and function within a proteinase K-resistant mitochondrial compartment. We identified Hax-1 (HS-1-associated protein X-1), a mitochondrial protein involved in the maintenance of mitochondrial membrane potential, as a GrB substrate within the mitochondrion. GrB cleaves Hax-1 into two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
(96 reference statements)
2
28
0
Order By: Relevance
“…Tagged complex I subunits overexpressed in the B-cell line 721.221, or MEF localized to the mitochondria and integrated into complex I (Supplementary Figures 1e-g and data not shown). GB induced a dose-and time-dependent cleavage of tagged NDUFV1, NDUFS2 and NDUFS1 similar to PARP-1 and HAX-1 11,12 cleavage (Supplementary Figures 2a-c). GB did not cleave NDUFS3, NDUFS7 or NDUFA13 (data not shown).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Tagged complex I subunits overexpressed in the B-cell line 721.221, or MEF localized to the mitochondria and integrated into complex I (Supplementary Figures 1e-g and data not shown). GB induced a dose-and time-dependent cleavage of tagged NDUFV1, NDUFS2 and NDUFS1 similar to PARP-1 and HAX-1 11,12 cleavage (Supplementary Figures 2a-c). GB did not cleave NDUFS3, NDUFS7 or NDUFA13 (data not shown).…”
Section: Resultsmentioning
confidence: 86%
“…2 GB causes reactive oxygen species (ROS) production, dissipation of the mitochondrial transmembrane potential (ΔΨm) and MOMP, which leads to the release of apoptogenic factors such as cytochrome c (Cyt c), HtrA2/Omi, endonuclease G (Endo G), Smac/Diablo and apoptosis-inducing factor, from the mitochondrial intermembrane space to the cytosol. [4][5][6][7][8][9][10][11] Interestingly, cells deficient for Bid, Bax and Bak are still sensitive to human GB-induced cell death, 5,[11][12][13] suggesting that human GB targets the mitochondria in another way that needs to be characterized. Altogether, much attention has been focused on the importance of MOMP in the execution of GB-mediated cell death, leaving unclear whether ROS production is a bystander effect or essential to the execution of GBinduced apoptosis.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] GB-induced cell death also involves Bid/Bax/ Bak-mediated mitochondrial outer membrane permeabilization for the release of the apoptogenic factors cytochrome c, Smac/Diablo, Endo G, HtrA2 and AIF. 1,[9][10][11][12][13][14][15][16][17] We have recently reported that mitochondrial reactive oxygen species (ROS) have a critical role in GB pathway by amplifying apoptogenic factor release, oligonucleosomal DNA fragmentation and lysosomal membrane rupture. 18 Mitochondrial ROS resulted from GB-mediated cleavage of NDUFV1, NDUFS1 and NDUFS2, three subunits of mitochondrial complex I.…”
mentioning
confidence: 99%
“…HAX1 is also subject to cleavage by granzyme B. 25 Whereas the N-terminal cleavage product localizes to mitochondria and mediates depolarization, the C-terminal cleavage product can be found in the cytosol. 25 HAX1 may interact with X-linked inhibitor of apoptosis, preventing polyubiquitination of X-linked inhibitor of apoptosis 1 and thus act to maintain viability.…”
Section: Scn3 (Hcls1-associated Protein X-1 [Hax1])mentioning
confidence: 99%
“…25 Whereas the N-terminal cleavage product localizes to mitochondria and mediates depolarization, the C-terminal cleavage product can be found in the cytosol. 25 HAX1 may interact with X-linked inhibitor of apoptosis, preventing polyubiquitination of X-linked inhibitor of apoptosis 1 and thus act to maintain viability. 26 In addition to a prominent role in protecting against cell death, HAX1 has also been reported to be involved in multiple other cellular functions, such as calcium homeostasis, cell motility and cytoskeletal rearrangement, and messenger RNA processing.…”
Section: Scn3 (Hcls1-associated Protein X-1 [Hax1])mentioning
confidence: 99%